Ethno-RSTEM Integrated E-Module Assisted by Virtual Reality to Provide Students with Chemical Literacy and Religious Values - Nurul Fadhilah; Sudarmin Sudarmin; Woro Sumarni (Jurnal Tadris Kimiya, 2026)
This research aimed to describe the characteristics of the e-module containing Ethno-RSTEM assisted by virtual reality, and analyze the feasibility and effectiveness of the e-module to provide students with chemical literacy and religious values. This research method used a 4D model (define, design, develop, disseminate). The instruments in this research consisted of test and non-test instruments. The e-module possessed characteristics in the form of local wisdom content in the city of Kudus, STEM and religious values. The e-module also presented 360-degree videos and Ethno-VR local wisdom of the city of Kudus. The e-module was considered suitable for classroom implementation based on expert evaluations of its content, media, and ethno-virtual reality components. The results of student responses to the e-module in the implementation phase obtained an average score of 68.5 ("Very Good" category), and the teacher's practicality questionnaire achieved an average score of 70.1 ("Very Practical" category). Furthermore, the e-module was effective in providing students with chemical literacy, with 6% of students achieving the "Very Good" category, 69% in the "Good" category, and 25% in the "Fair" category. It also enhanced religious values as indicated by an average score of 59.91 ("Very Religious" category).